Terpenoids from the leaves and stems of Dysoxylum tpongense - Khanh, Pham Ngoc; Tai, Bui Huu; Huong, Tran Thu; Cuong, To Dao; Hai, Ha Viet; Luong, Ngo Xuan; Kim, Young Ho; Cuong, Nguyen Manh (Vietnam Journal of Science and Technology, 2019)
Study on chemical constituents from the leaves and stems of Dysoxylum tpongense Pierre resulted in the isolation of six known compounds (1–6). The chemical structures of isolated compounds were identified as cabraleahydroxylactone (1), cabraleahydroxylactone-3-acetate (2), (+) spathulenol (3), b-sitosterol (4), stigmasterol (5), and stigmast-4-en-3-one (6) by comparison of the physicochemical, interpretation of NMR and mass spectral data with that reported in the literature.